Effects of Phonophoresis with Hydrocortisone Alone and in Combination with 10% Dimethylsulfoxide on Myofascial Trigger Points in the Upper Trapezius Muscle - Roostayi, Mohammad Mohsen; Tajammoli, Zahra; Ghasemi, Mehri; khademi kalantari, Khosro; Akbarzadeh-Baghban, Alireza (Journal of Clinical Physiotherapy Research, 2019)
Dimethylsulfoxide is a potent solvent which is used to increase the transdermal transport of medicines. The aim of this study was to examine the effects of phonophoresis with hydrocortisone alone and in combination with dimethylsulfoxide on the upper trapezius trigger points. Sixty patients were divided into three groups and received ten treatment sessions with different protocols using ultrasound: 1% hydrocortisone gel, a solution of 10% dimethylsulfoxide and 1% hydrocortisone gel, and a neutral ultrasound gel. The pain, pressure pain threshold, and the range of motion of the neck were assessed at four intervals in all three groups. The results revealed that phonophoresis with the two treatment gels and ultrasound with neutral gel significantly reduced the pain and the pressure pain threshold (P=0.01). The range of ipsilateral lateral flexion and contralateral lateral flexion of the neck was significantly improved following phonophoresis with 10% DMSO and 1% hydrocortisone gel (P=0.01 and P=0.02, respectively). Thus, it was concluded that the addition of 10% DMSO to 1% hydrocortisone gel enhanced the persistence of the beneficial effects of hydrocortisone on the pain, pressure pain threshold, and the range of motion of the neck. Keywords: Myofascial trigger point, Phonophoresis, Hydrocortisone, Dimethylsulfoxide